ผลของการจัดการเรียนรู้พลศึกษาโดยใช้โปรแกรมการออกกำลังกายด้วยยางยืดที่มีต่อสมรรถภาพทางกายที่สัมพันธ์กับสุขภาพของนักเรียนมัธยมศึกษาตอนต้น - ธาตรี ดีประดวง (จุฬาลงกรณ์มหาวิทยาลัย, 2013)
The purposes of this research were to study and to compare the effects of physical education learning management using an exercising program by using elastic band on health-related physical fitness of lower secondary school students. The subjects in the study were a group of 40 students that aged between 13-15 years old. These students were divided equally into two groups: a control group and an experimental group. The health-related physical fitness of all of the students were measured both before and after the experiment. The experimental group exercised for 60 minutes a day, 3 days a week for a period of 8 weeks. The obtained data were then statistically analyzed in terms of the mean, standard deviation, and a t-test was employed to determine the significance of the differences at the .05 level. The results of the research were as follows :1) After the experiment the total indicators of health-related physical fitness in the experimental group were significantly higher level than before the experiment at the .05 level.2) After the experiment the indicators of health-related physical fitness in the experimental group were at a significantly higher level than the control group at the .05 level.